MAXIMUM ENTROPY (MAXENT) MODELLING FOR PREDICTING THE POTENTIAL DISTRIBUTION OF PHLOEOSINUS AUBEI (PERRIS, 1855) (COL.: CURCULIONIDAE, SCOLYTINAE) AS RISING THREAT FOR CUPRESSUS SEMPERVIRENS L. TREES IN TURKEY - Orucu, Omer Kamil; Sen, Ismail; Sarıkaya, Oğuzhan (Health & Environment Assoc, 2019)
Cupressus sempervirens is one of the main elements of the cultural landscape of the Mediterranean coast. It can be preferred for the purpose of closing the unwanted views as aesthetic and decorative, reinforcing the beauty of the landscape, increasing the value of architectural works and historical works. Phloeosinus aubei (Perris, 1855) is an important bark beetle species (Col.: Curculionidae, Scolytinae) that attacks to the Cupressaceae family. It was determined as an important pest of cypress in some European countries. Also, it is observed that the expantion and epidemy potential of P. aubei has been increasing especially through to the Mediterranean region of Turkey on Cupressus sempervirens, Juniperus communis, J. excelsa and Thuja species in Turkey. This study was conducted to modelling the current and future (2050 and 2070) distributions of Phloeosinus aubei in Turkey according to RCP4.5 and RCP8.5 (Representational Concentration Pathways) climate change scenarios. Results showed that Phloeosinus aubei will expand its range towards Aegean region of Turkey.
Keywords: Cupressus sempervirens; Phloeosinus aubei; Maxent; predicting